Environmental cadmium exposure aggravates renal fibrosis and reduced renal lipid accumulation in diabetic mice - Changhao Li; Fuda Dong; Yilimilai Dilixiati; Yunbin Bai; Zengli Zhang (Lipids in Health and Disease)
Abstract Background Cadmium (Cd) is a heavy metal with nephrotoxicity. While the harmful effects of Cd exposure on the kidney have been extensively studied, the nephrotoxicity of Cd exposure on diabetic individual remain largely unexplored. Given the widespread Cd pollution and the high prevalence of diabetes, it is imperative to explore the nephrotoxicity and underlying mechanism of Cd exposure on diabetic individual. Methods In current study, established diabetic mouse and high glucose cultured HK-2 cells were exposed to CdCl2 (50 ppm in vivo, 10 µM in vitro). Renal fibrosis and renal lipid accumulation were studied in Cd-exposed diabetic mice and high glucose cultured HK-2 cells. Additionally, qRT-PCR and Western blot were used to evaluate renal fibrosis and lipid metabolism related gene and protein. Results Present study showed no significant nephrotoxicity in Cd-exposed healthy mice and Cd-exposed HK-2 cells. However, same dosing Cd activated TGF/SMAD signaling pathway and increased collagen deposition in kidney of diabetic mice and high glucose cultured HK-2 cells. Intriguingly, Cd reduced renal lipids deposition and inhibited fatty acid synthesis both in diabetic mice and high glucose cultured HK-2 cells. Conclusions Overall, our findings demonstrate that low dosing Cd significantly aggravated renal fibrosis in diabetic mice and high glucose cultured HK-2 cells. It is recommended that diabetic individuals should avoid working in Cd pollution environment and consuming cadmium-contaminated food. Furthermore, we found that Cd reduced lipid deposition in kidney of diabetic mice and high glucose cultured HK-2 cells. The results provide novel insights into renal lipid metabolism in Cd-exposed diabetic individuals.